1998
DOI: 10.1097/00001756-199808030-00025
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of Bcl-2 expression

Abstract: Neuroprotective effects of estrogen have been demonstrated against a variety of cytotoxic insults. We present data here addressing a possible mechanism of estrogen neuroprotection in the human teratocarcinoma cell line NT2 terminally differentiated to a neuronal phenotype. Cell death induced by H2O2 or glutamate results in a dose-dependent cell death of NT2 neurons, while 24 h of estrogen pretreatment significantly enhances neuronal viability. Bcl-2 expression has been shown to reduce oxidative stress and prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 159 publications
(15 citation statements)
references
References 12 publications
2
13
0
Order By: Relevance
“…E2 exerts neuroprotective action in various model systems where it reduces neuronal damage caused by serum deprivation (43,44), ␤-amyloid treatment (45,46), and exposure to glutamate (46,47). In the present study we found that E2 protects HiB5 cells against toxicity induced by AMPA and A␤ peptide.…”
Section: Discussionsupporting
confidence: 61%
“…E2 exerts neuroprotective action in various model systems where it reduces neuronal damage caused by serum deprivation (43,44), ␤-amyloid treatment (45,46), and exposure to glutamate (46,47). In the present study we found that E2 protects HiB5 cells against toxicity induced by AMPA and A␤ peptide.…”
Section: Discussionsupporting
confidence: 61%
“…Estradiol prevents cell death by the regulation of genes related to apoptosis [16]. Our results showed that the level of Bcl-2 was decreased in ischemic damage region, whereas the level of Bax was significantly increased.…”
supporting
confidence: 46%
“…T regulates the expression of antiapoptotic genes such as bcl-2 in the spinal nucleus of the bulbocavernosus in male rats (42). 17␤-Estradiol (E 2 ), a metabolite of T, promotes the expression of several antiapoptotic genes (43)(44)(45)(46)(47)(48). In zebra finches, neuronal injury is accompanied by an increase in expression of aromatase, an enzyme that converts T to E 2 (49), and inhibition of aromatase increases apoptosis near the injury (50).…”
Section: Discussionmentioning
confidence: 99%